2017
DOI: 10.1371/journal.pone.0173263
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the vitamin D pathway CYP2R1 gene predicts sustained HBeAg seroconversion in chronic hepatitis B patients treated with pegylated interferon: A multicenter study

Abstract: Evidence of a role of vitamin D in the immune system is increasing. Low serum vitamin D is associated with increased hepatitis B virus replication. Genome-wide association study (GWAS) data has revealed a number of the single nucleotide polymorphisms (SNPs) within the vitamin D synthetic pathway that affect vitamin D functions. We aimed to determine the association between SNPs in the vitamin D gene cascade and response to pegylated interferon (PegIFN) therapy in hepatitis B e-antigen (HBeAg)-positive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
(48 reference statements)
1
22
0
Order By: Relevance
“…But some research showed contradictive results. 28,29 18 Another study in Thailand also showed genotype of CYP27B1 rs4646536 predicted the clinical outcome of CHB patients. 30 In a retrospective cohort of HBeAg-negative patients from Italy, VDR rs7975232/ApaI genotype was the independent predictor of clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But some research showed contradictive results. 28,29 18 Another study in Thailand also showed genotype of CYP27B1 rs4646536 predicted the clinical outcome of CHB patients. 30 In a retrospective cohort of HBeAg-negative patients from Italy, VDR rs7975232/ApaI genotype was the independent predictor of clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies on the association between vitamin D‐related genetic factors and response to Peg‐IFN in CHB infection have been reported yet. In a latest retrospective multicenter study, CYP2R1 rs12794714 polymorphism was determined to be genetic predictor of sustained HBeAg clearance after Peg‐IFN therapy in HBeAg‐positive CHB patients in Thailand . Another study in Thailand also showed genotype of CYP27B1 rs4646536 predicted the clinical outcome of CHB patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there have been other prior studies examining the durability of HBeAg seroconversion in patients treated with PEG‐IFN, they have largely been limited by lack of long‐term follow‐up, small sample size, and/or involvement of other treatment medications . In our literature review, there was only one other study with more than 10 patients that reported follow‐up greater than 1 year (Ratnam et al), but this study was limited to just 2‐year follow‐up (Table ) …”
Section: Overall Durable and Delayed Seroconversion Rates Of Chronicmentioning
confidence: 97%